SEJARAH PERKEMBANGAN PARIWISATA GEOSITE SIPINCUR SEBAGAI DESTINASI SUPER PRIORITAS WISATA DI HUMBANG HASUNDUTAN - Diansyah, Arfan; Simamora, Rapmaita Lamaida; Pakpahan, Juliyanti; Sinurat, Ika; Daulay, Dwirja Aditya; Sidabutar, Beatrix (Puteri Hijau : Jurnal Pendidikan Sejarah, 2024)
The Sipincur Geosite is one of the Toba calderas in Humbang Hasundutan, precisely in Pearung Village, Paranginan District. Sipincur Geosite is a natural tourist destination filled with Tusam (pine) plants. A tourist destination that offers beautiful natural views, plants and Lake Toba, makes the Sipincur Geosite visited by many tourists. The opening of the Sipincur Geosite started at the same time as Humbang Hasundutan from North Tapanuli bloomed in 2003. The Sipincur Geosite, which is taken from the word "Pincur" which means steep, makes people or visitors want to see Lake Toba directly. Over time, the development and provision of facilities has resulted in the Sipincur Geosite having a positive impact on the community and government. The existence of Lake Toba, which was made by President Joko Widodo as a priority destination, and the inclusion of Lake Toba as a National and International Geopark, has made Sipincur a priority destination and icon for Humbang Hasundtan Regency. The aim of this research is to find out what is the history and development of the Sipincur Geosite tourist destination as an icon and priority destination for Humbang Hasundutan Regency? The method used in this research is qualitative literature study, by conducting reviews through books, journals or websites, which are supported by facts from Humbang Hasundutan tourism service sources.